2013
DOI: 10.1037/a0030500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immigration and acculturation on victimization among a national sample of Latino women.

Abstract: The current study examined the effect of immigrant status, acculturation, and the interaction of acculturation and immigrant status on self-reported victimization in the United States among Latino women, including physical assault, sexual assault, stalking, and threatened violence. In addition, immigrant status, acculturation, gender role ideology, and religious intensity were examined as predictors of the count of victimization among the victimized subsample. The Sexual Assault Among Latinas (SALAS) Study sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 82 publications
(153 reference statements)
2
89
1
Order By: Relevance
“…Overall, the intersection of previous literature and the current research suggests that the current findings are somewhat dissimilar from those found by Le and Wallen (2009) on intraethnic Asian victimization. In addition, compared to research sampling similar ethnic groups (e.g., Le & Wallen, 2009) as well as different ethnic groups (e.g., Sabina et al, 2012) the current sample of immigrants experienced a higher prevalence of victimization. In sum, while findings in the current research are not supportive of intraethnic differences in victimization, future studies should not disregard disaggregating ethnic groups since valuable contextual information may actually exist between groups (e.g., Zhou & Xiong, 2005).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Overall, the intersection of previous literature and the current research suggests that the current findings are somewhat dissimilar from those found by Le and Wallen (2009) on intraethnic Asian victimization. In addition, compared to research sampling similar ethnic groups (e.g., Le & Wallen, 2009) as well as different ethnic groups (e.g., Sabina et al, 2012) the current sample of immigrants experienced a higher prevalence of victimization. In sum, while findings in the current research are not supportive of intraethnic differences in victimization, future studies should not disregard disaggregating ethnic groups since valuable contextual information may actually exist between groups (e.g., Zhou & Xiong, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…One side of research using comparative analyses of immigrants and native-born persons has highlighted that the former may experience significantly less victimization than the latter (e.g., Perreault, 2004;Sabina, Cuevas, & Schally, 2012). Results from Sabina and colleagues (2012) showcased significantly lower levels for any type of victimization-such as stalking, physical, sexual, and threats-reported by Hispanic immigrants when compared with natural-born U.S. citizens.…”
Section: Immigrant Victimizationmentioning
confidence: 99%
“…This finding suggests that, although prior experiences, including violence, conflict, and forced migration, may contribute to some extent, other factors, such as family cohesion, hope, opportunity, settlement supports, and living in urban centers with high-density immigrant communities (associated with reduced crime and better health outcomes), may contribute to our findings. 8,[27][28][29] We found that with increasing time since migration, there was no change in risk of experiencing violence. Other studies have found that time since migration is associated with increasing perpetration of violence, increasing substance use, and increasing intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 of 14 quantitative studies included an all undocumented sample. Among studies in which only a portion of the sample was undocumented (14 of 24), the percentage of UIs in the total sample ranged from 5% to 93%, with the lowest percentage including UIs recruited via a nationwide randomdigit-dial survey (Sabina, Cuevas, & Schally, 2013), and the highest from an all female sample recruited from a home visiting program (Paris, 2008).…”
Section: Participant Characteristicsmentioning
confidence: 99%